The Economic Worth of Product Placement in Prime-time Television Shows1. (March 2016) - Begy, Genevieve; Talwar, Vishal
Product placement is fiercely being courted by firms as a consequence of the declining credibility of traditional broadcast advertising and the '30-second spot'. Very little research analysing its economic worth exists outside of the realm of film, however. This paper responds by applying a consistent measure of placement effectiveness to television through use of event analyses. It finds a mean cumulative abnormal return of 0. 79% in a sample of 264 placements from the 2011-12 prime-time season, confirming that product placement in television is positively and significantly associated with movement in firms' stock prices. Placement in a season premiere has significantly higher mean returns than in a non-pivotal episode, irrespective of whether the firm places the product in both episodes. A cross-sectional analysis of placement, episode and show factors suggests that the duration of placement and one-hour show length are positively associated with stock price movement. Placement in a show's debut season is adversely associated to worth.